PRACTICAL OPPORTUNITIES TO PREPARING STUDENTS FOR CONSTRUCTIVE ACTIVITIES (American Journal of Pedagogical and Educational Research, 2024)
In this article, in the process of preparing students of higher education institutions for constructive activity, the possibilities of developing a model of person-oriented relations, acquiring methodological tools, understanding, accepting and implementing a humanitarian position have been revealed.